Susceptibility of Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae) Mediterranean Populations Found in São Paulo, Brazil to 11 Insecticides and Characterization of Their Endosymbionts - Alvarez, Daniel de Lima [UNESP] (2024)
The silverleaf whitefly, Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae), is a significant agricultural pest worldwide, impacting a variety of crop yields. Since the introduction of B. tabaci Mediterranean (MED) species in Brazil, limited research has measured the relative efficacy of the primary insecticides used in whitefly management. This study evaluated the susceptibility of three distinct B. tabaci MED populations to 11 insecticide active ingredients and characterized the bacterial endosymbionts within each population. The insecticides tested were acetamiprid, bifenthrin, cyantraniliprole, diafenthiuron, spiromesifen, imidacloprid, pymetrozine, pyriproxyfen, sulfoxaflor, and thiamethoxam. Results showed varying LC50 and LC90 values among tested insecticides and populations. Notably, populations varied in response to imidacloprid and thiamethoxam with some populations having a 6× higher tolerance. Sequencing data of endosymbionts revealed that individuals from the most susceptible B. tabaci population harbored Rickettsia and Arsenophonus, whereas these bacteria were not detected in the resistant populations. These findings highlight the need for frequent insecticide toxicity bioassays of distinct B. tabaci populations and the adoption of integrated pest management strategies to preserve the efficacy of insecticides for B. tabaci control. Additionally, the role of infection by endosymbionts to alter susceptibility should be further explored.